In the pursuit of equality: philosophical principles of affirmative actions in Social Policy - Arias Arias, Eunice (2025)
Social policy, by itself, has different intrinsic principles that lead to the improvement of democracy in the country. Public policies in this field seek the reduction of specific privileges, which would lead to fair and equitable access to rights. In this regard, Mexico is taken as a case study to formulate public policy proposals that seek the effective incorporation of historically discriminated populations, and that, in addition, recognize the principle of equality as a normative foundation towards the search for a minimum floor guaranteed by the State, such as the Universal Basic Income (IBU, by its Spanish acronym) in our country.